Posterior Interosseous Nerve Entrapment in a Patient with Rheumatoid Arthritis - Korhan BAKLACI; Ahmet ÖZGÜL2 (Archives of Rheumatology, 2012)
Posterior interosseous nerve entrapment is a rare complication of rheumatoid arthritis (RA), a chronic, systemic inflammatory disorder which principally involves the synovial joints. In this article, we present a case of posterior interosseous nerve lesion associated with rheumatoid synovial cysts of the elbow joint. According to literature survey our report is the first case in which posterior interosseous nerve entrapment was cured with a full recovery using conventional methods without any surgical intervention. This recovery was confirmed through imaging methods including magnetic resonance imaging, musculoskeletal ultrasound, and electromyography during 18-month follow-up.